¿Qué factores determinan la distribución altitudinal de los peces de ríos tropicales andinos? - De la Barra, Evans (2016)
Altitudinal gradients represent an appropriate system to assess whether there is a relationship between richness patterns, environmental variables, and the ecological processes that determine the species type and number inhabiting a given area. In mountain streams freshwater fishes, the most prevalent relationship is a monotonic decrease in species richness with elevation. The objective of this study was to evaluate four hypotheses that can explain the negative relationship between local fish species richness and altitude, 1) the hypothesis of decreasing energy availability, 2) the hypothesis of increasing climate severity, 3) the hypothesis of habitat diversity, and 4) the hypothesis of isolation by physical severity of the environment. Fish and macro-invertebrates were collected following standard methods from 83 sites (between 200-4 000 meters) of two river basins in the Bolivian Amazon. The first hypothesis was tested by analyzing relationships between the density of macro-invertebrates, the richness of invertivorous fish species and altitude; while the second and third hypotheses were assessed by a multiple regression analysis (GLM) between fish species richness and several local and regional factors. Besides, assemblage dissimilarity between sites along the altitudinal gradient was analyzed using βsim and βness indices. Fish richness decreases linearly with increasing altitude. The density of macro-invertebrates tends to increase at higher altitudes, contrary to invertivorous fish species richness, suggesting that energy availability is not a limiting factor for fish species colonization. The GLM explained 86% of the variation in fish species richness, with a significant contribution of water temperature, maximum slope in the river mainstem, and stream width. There is a higher species turnover (βsim) between sites at low elevation. Inversely, βness shows higher values in the upper parts, corresponding to change in assemblages mainly due to species loss. Taken together, these results suggest that climatic and physical severities create strong barriers to colonization, further explaining the decrease in fish richness along the altitudinal gradient.